A narrative review of the epidemiology and economics of chronic wounds. (21st September 2021) - Graves, N.; Phillips, C.J.; Harding, K.
Summary: Chronic wounds have a debilitating effect on the quality of life of many individuals, and the large economic impact on health system budgets warrants greater attention in policy making and condition management than is currently evident. The aim of this narrative review is to summarize the nature and extent of the chronic wound problem that confronts health systems across the world. The first section is used to highlight the underlying epidemiology relating to chronic wounds, while the second explores the economic costs associated with them and the relative efficiency of measures designed to manage them.